Serious Complications Related to Obstetric Anesthesia: The Serious Complication Repository Project of the Society for Obstetric Anesthesia and Perinatology. Issue 3 (September 2015) - D'Angelo, R.; Smiley, R.M.; Riley, E.T.; Segal, S.
Abstract : ( Anesthesiology. 2014; 120:1505–1512)